Relação entre controle familiar e a manutenção do posicionamento estratégico das companhias listadas na BM&FBovespa - Olesiak, Estevo Mateus (Universidade do Vale do Rio dos Sinos, 2018)
This study aimed to analyze the relationship between family control and the maintenance of strategic positioning in companies listed on BM & FBovespa. For this purpose, a survey was carried out in the Management Reports (RA), Reference Forms and Financial Statements for the financial year 2002 to 2016 of 110 companies from various sectors, as well as a survey of the family control provided by them. For the categorization of RA data, a list of categories and subcategories was used based on the strategic positions cost and differentiation, already validated in previous studies, through the Delphi Technique. The speeches on family strategy and level of control, after categorized, were analyzed using Spearman's correlation analysis and the Kruskal-Wallis test. The results allow to consider the non-proof of the central hypothesis of the research, since it was expected negative correlation between the variables, so that the higher the family insertion in the control, the lower the variation between strategies, which did not occur. Nonetheless, the results showed a positive but weak correlation between family control and speech variation between strategies. The analysis by sector again did not prove the hypothesis in any sector, however, it reaffirmed the findings in the overall analysis. The existence of such a positive correlation suggests two interpretations: first, the existence of generational exchanges in the control and / or management of family businesses, which may encourage changes in strategies as already suggested in previous studies. The second interpretation considers that the lower bureaucracy in family businesses enables families to interfere in management reports to justify changes in economic and / or financial indices in the name of maintaining the image / reputation of the institution. This reaffirms, in part, the long-term vision, and greater interest in the image, and continuity of the family business. In addition to the immediate results, the research provides other contributions, such as the negative correlation between "state control" and "variation of the discourse between strategies", demonstrating that the greater the state control, the less the variation of the discourse between strategies. Other contributions show a negative correlation between family control and total speech in 15 years, evidencing that the higher the family control the less the amount of strategy speech over the years.
Keywords: Controle familiar; Posicionamento estratégico; Discurso de estratégia; Family control; Strategic positioning; Strategy speech; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis